Exploring Challenges Faced by English Language Teachers: Voices from EFL Teachers in Indonesia - Sebayang, F Ari Anggraini; Basri, Muh. Hasan; Rambing, Rosalina Rolany; Yulianty Sanggelorang (ETERNAL (English Teaching Journal), 2025)
Playing a vital role in EFL education, teachers often encounter challenges when teaching students English. This study focuses on exploring challenges faced by EFL teachers in Indonesia. The study was conducted through qualitative research design with a case study approach. A total of 5 male and female EFL teachers in senior high schools in North Sulawesi participated in interview sessions during the data collection. A semi-structured interview was conducted to obtain comprehensive descriptions of teachers’ challenges in teaching English in EFL context. The interview data was transcribed, coded, and grouped to decide the themes. The findings indicated that the primary challenges they encountered when teaching EFL including demotivated students, excessive working hours, numerous obligations, improper utilization of technology by students, and governmental expectations resulted from the Merdeka Curriculum. These results suggest complex problems experienced by teachers in Indonesia. Understanding teachers’ challenges in EFL education give insights to stakeholders, including policy maker and curriculum developers to optimize EFL education in Indonesia.